Efeito de uma Pseudomonas sp. oligonitrófila na estabilidade de agregados do solo - Gomide Loures, Emílio; Reis Condé, Alcides; de Alencar, José (Revista Ceres, 2025)
The capacity of a Pseudomonas sp. which showed oligonitrophilous features to aggregate soil particles was tested in vitro.